The emergent rhizosphere: imaging the development of the porous architecture at the root-soil interface - Helliwell, J.R.; Sturrock, Craig J.; Mairhofer, Stefan; Craigon, Jim; Ashton, R.W.; Miller, A.J.; Whalley, W.R.; Mooney, Sacha J. (Nature Publishing Group, 2017)
The rhizosphere is the zone of soil infuenced by a plant root and is critical for plant health and nutrient acquisition. All below ground resources must pass through this dynamic zone prior to their capture by plant roots. However, researching the undisturbed rhizosphere has proved very challenging. Here we compare the temporal changes to the intact rhizosphere pore structure during the emergence of a developing root system in diferent soils. High resolution X-ray Computed Tomography (CT) was used to quantify the impact of root development on soil structural change, at scales relevant to individual micro-pores and aggregates (µm). A comparison of micro-scale structural evolution in homogenously packed soils highlighted the impacts of a penetrating root system in changing the surrounding porous architecture and morphology. Results indicate the structural zone of infuence of a root can be more localised than previously reported (µm scale rather than mm scale). With time, growing roots signifcantly alter the soil physical environment in their immediate vicinity through reducing root-soil contact and crucially increasing porosity at the root-soil interface and not the converse as has often been postulated. This ‘rhizosphere pore structure’ and its impact on associated dynamics are discussed.